Islamic Education Management In The Society 5.0 Era: Building A Educational System That Is Responsive To Technological And Social Changes - Qur Rohman; Agus Fawait; Ahmadi Pramuja (Journal of International Multidisciplinary Research, 2025)
This research aims to analyze Islamic education management in facing the Society 5.0 era, characterized by the integration of digital technology in social and educational life. Using a mixed-methods approach, this research collected quantitative data through surveys of 150 respondents from Islamic educational institutions and qualitative data through in-depth interviews with 15 school principals and pesantren administrators. The research results show that although technology has been adopted by most Islamic educational institutions, significant challenges arise related to infrastructure limitations, teachers' digital skills, and access disparities in various regions. Adaptive and technology-based leadership plays a crucial role in designing policies that support digital transformation in Islamic educational institutions. Moreover, the integration of Islamic values with technology has also proven to be important in maintaining the identity and morality of Islamic education. This research suggests the importance of intensive training for educators and equitable access to technology so that Islamic education management can be more responsive to social and technological changes, and capable of improving the quality of education in the future.